Lebensformen, Welt, Gesellschaft. Normen und Werte - Religionen und Kulturen. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Mensch, Natur, Technik. Lebenswelt, Information und Sprache. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Neural Network-Based Demand-Side Management in a Stand-Alone Solar PV-Battery Microgrid Using Load-Shifting and Peak-Clipping - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Energies)
Due to failures or even the absence of an electricity grid, microgrid systems are becoming popular solutions for electrifying African rural communities. However, they are heavily stressed and complex to control due to their intermittency and demand growth. Demand side management (DSM) serves as an option to increase the level of flexibility on the demand side by scheduling users’ consumption patterns profiles in response to supply. This paper proposes a demand-side management strategy based on load shifting and peak clipping. The proposed approach was modelled in a MATLAB/Simulink R2021a environment and was optimized using the artificial neural network (ANN) algorithm. Simulations were carried out to test the model’s efficacy in a stand-alone PV-battery microgrid in East Africa. The proposed algorithm reduces the peak demand, smoothing the load profile to the desired level, and improves the system’s peak to average ratio (PAR). The presence of deferrable loads has been considered to bring more flexible demand-side management. Results promise decreases in peak demand and peak to average ratio of about 31.2% and 7.5% through peak clipping. In addition, load shifting promises more flexibility to customers.
Keywords: Energy (miscellaneous); Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Electrical and Electronic Engineering; Control and Optimization; Engineering (miscellaneous); Building and Construction

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

High-speed hyperspectral imaging of ferroelectric domain walls using broadband coherent anti-Stokes Raman scattering - Reitzig, Sven; Hempel, Franz; Ratzenberger, Julius; Hegarty, Peter A.; Amber, Zeeshan H.; Buschbeck, Robin; Rüsing, Michael; Eng, Lukas M. (Applied Physics Letters)
Spontaneous Raman spectroscopy (SR) is a versatile method for analysis and visualization of ferroelectric crystal structures, including domain walls. Nevertheless, the necessary acquisition time makes SR impractical for in situ analysis and large scale imaging. In this work, we introduce broadband coherent anti-Stokes Raman spectroscopy (B-CARS) as a high-speed alternative to conventional Raman techniques and demonstrate its benefits for ferroelectric domain wall analysis. Using the example of poled lithium niobate, we compare the spectral output of both techniques in terms of domain wall signatures and imaging capabilities. We extract the Raman-like resonant part of the coherent anti-Stokes signal via a Kramers–Kronig-based phase retrieval algorithm and compare the raw and phase-retrieved signals to SR characteristics. Finally, we propose a mechanism for the observed domain wall signal strength that resembles a Čerenkov-like behavior, in close analogy to domain wall signatures obtained by second-harmonic generation imaging. We, thus, lay here the foundations for future investigations on other poled ferroelectric crystals using B-CARS.
Keywords: Physics and Astronomy (miscellaneous)

Tuning domain wall conductivity in bulk lithium niobate by uniaxial stress - Singh, Ekta; Beccard, Henrik; Amber, Zeeshan H.; Ratzenberger, Julius; Hicks, Clifford W.; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Conductive domain walls (DWs) in insulating ferroelectrics have recently attracted considerable attention due to their unique topological, optical, and electronic properties, and offer potential applications such as in memory devices or rewritable circuitry. The electronic properties of DWs can be tuned by the application of strain, hence controlling the charge carrier density at DWs. In this paper, we study the influence of uniaxial stress on the conductivity of DWs in the bulk single crystal lithium niobate (LiNbO3). Using conductive atomic force microscopy, we observe a large asymmetry in the conductivity of DWs, where only negatively screened walls, so called head-to-head DWs, are becoming increasingly conductive, while positively screened, tail-to-tails DWs, show a decrease in conductivity. This asymmetry of DW conductivity agrees with our theoretical model based on the piezoelectric effect. In addition, we observed that the current in the DW increases up to an order of magnitude for smaller compressive stresses of 100 MPa. This response of DWs remained intact for multiple stress cycles over two months, opening a path for future applications.

Nanoscale Conductive Sheets in Ferroelectric BaTiO3: Large Hall Electron Mobilities at Head-to-Head Domain Walls - Beccard, Henrik; Kirbus, Benjamin; Beyreuther, Elke; Rüsing, Michael; Bednyakov, Petr; Hlinka, Jiří; Eng, Lukas M. (ACS Applied Nano Materials)
Strongly charged head-to-head domain walls that are purposely engineered along the [110] crystallographic orientation into ferroelectric BaTiO3 single crystals have been proposed as intrinsically nanoscaled two-dimensional electron gases (2DEGs) because of their significant conductivity. Here, we quantify these 2DEG properties through dedicated Hall transport measurements in van der Pauw 4-point geometry, finding the electron mobility to reach around 400 cm2 (V s)^{−1}, while the two-dimensional charge density amounts to 7 × 103 cm^{–2}. We underline the necessity to take into account the thermal and geometrical misalignment offset voltages by evaluating the Hall resistance under magnetic field sweeps; otherwise, errors of several hundred percent in the derived transport parameters can occur.
Keywords: General Materials Science

Investigation of ferroelectric domain walls in periodically-poled LiNbO3 single crystals by polarization-sensitive optical coherence tomography - Golde, Jonas; Rüsing, Michael; Kindler, Richard; Steuer, Svea; Rix, Jan; Eng, Lukas M.; Koch, Edmund (Optical Components and Materials XIX)

Nonlinear optical interactions in focused beams and nanosized structures - Amber, Zeeshan H.; Spychala, Kai J.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film materials from μm thickness down to single-atomic-layered 2D materials play a central role in many novel electronic and optical applications. Coherent, nonlinear optical (NLO) μ-spectroscopy offers insight into the local thickness, stacking order, symmetry, or electronic and vibrational properties. Thin films and 2D materials are usually supported on multi-layered substrates leading to (multi-)reflections, interference, or phase jumps at interfaces during μ-spectroscopy, which all can make the interpretation of experiments particularly challenging. The disentanglement of the influence parameters can be achieved via rigorous theoretical analysis. In this work, we compare two self-developed modeling approaches, a semi-analytical and a fully vectorial model, to experiments carried out in thin-film geometry for two archetypal NLO processes, second-harmonic and third-harmonic generation. In particular, we demonstrate that thin-film interference and phase matching do heavily influence the signal strength. Furthermore, we work out key differences between three and four photon processes, such as the role of the Gouy-phase shift and the focal position. Last, we can show that a relatively simple semi-analytical model, despite its limitations, is able to accurately describe experiments at a significantly lower computational cost as compared to a full vectorial modeling. This study lays the groundwork for performing quantitative NLO μ-spectroscopy on thin films and 2D materials, as it identifies and quantifies the impact of the corresponding sample and setup parameters on the NLO signal, in order to distinguish them from genuine material properties.<
Keywords: General Physics and Astronomy

Ba(BO2OH) – A Monoprotonated Monoborate from Hydroflux Showing Intense Second Harmonic Generation - Li, Yuxi; Hegarty, Peter A.; Rüsing, Michael; Eng, Lukas M.; Ruck, Michael (Zeitschrift für anorganische und allgemeine Chemie)
Abstract Pure samples of colorless, air‐stable Ba(BO 2 OH) crystals were obtained from Ba(NO 3 ) 2 and H 3 BO 3 under the ultra‐alkaline conditions of a KOH hydroflux at about 250 °C. The product formation depends on the water‐base molar ratio and the molar ratio of the starting materials. B(OH) 3 acts as a proton donor (Brønsted acid) rather than a hydroxide acceptor (Lewis acid). Ba(BO 2 OH) crystallizes in the non‐centrosymmetric orthorhombic space group P 2 1 2 1 2 1 . Hydrogen bonds connect the almost planar (BO 2 OH) 2− anions, which are isostructural to HCO 3 − , into a syndiotactic chain. IR and Raman spectroscopy confirm the presence of hydroxide groups, which are involved in weak hydrogen bonds. Upon heating in air to about 450 °C, Ba(BO 2 OH) dehydrates to Ba 2 B 2 O 5 . Moreover, the non‐centrosymmetric structure of Ba(BO 2 OH) crystals was verified with power‐dependent confocal Second Harmonic Generation (SHG) microscopy indicating large conversion efficiencies in ambient atmosphere.
Keywords: Inorganic Chemistry